Boxing techniques based on the analysis of boxing tournament finals during Olympic Games in London in 2012 - Kruszewski, M.; Kruszewski, A.; Kuzmicki, S.; Sklepinski, L.; Kepa, G.; Landowski, K. (Journal of Combat Sports and Martial Arts, 2016)
Introduction. The goal of the study was to indicate the changes in boxing techniques connected with the automated boxing scoring system (ABSS), based on the observation of boxing Finals during the Olympic Games in London in 2012. Material and methods. 10 final bouts were subjected to analysis and observation results were recorded in offense and defense sheets, including the division into rounds. The collected material was then subjected to analysis including to the most often used boxers` stances, the number and types of offensive techniques as well as the number and types of defensive techniques. Results. The fighters, moving in the mirror reverse of the norm (southpaw stance) won more often and most of the punches were thrown during the second and the third round. Jabs were thrown most often while hooks and uppercuts were thrown significantly less often. Punches in the trunk were thrown very rarely; short series of punches were thrown significantly more often (four times) than the series of long punches. Blocked defense was used most often and defense through counterpunch and footwork were the second most frequent techniques. No parrying defense was used. Conclusions. Due to the judge`s preferences, some attack techniques with the highest probability of recording were used significantly more often. Parrying defense is preferred as it does not entail the risk of accidental scoring by the judge.